A comment on Case C-324/17, Gavanozov, 24 October 2019: The Principle of Mutual Recognition versus Fundamental Rights - Castilhos, Daniela Serra; Pacheco, Fátima; Barata, Mário Simões (Revista Jurídica Portucalense, 2020)
The article seeks to analyze and comment the decision resulting from the Case (C-324/17, Gavanozov, 24 October 2019), which constitutes the first decision of the Court of Justice of the European Union in relation to the European Investigation Order. To this end, it intends to provide a framework for judicial cooperation in criminal matters and the principle of mutual recognition. We begin by analyzing Directive 2014/41/EU that approved the European Investigation Order (EIO), integrating it in the Area of ​​Freedom, Justice and Security. The reasons for non-recognition or non-execution of an EIO are also considered, namely those related to fundamental rights. Finally, the dispute and the question referred, as well as the Opinion of the Advocate General, are analyzed with a view to assessing whether, in this case, there was a violation of fundamental rights, namely Articles 47 and 48 of the Charter of Fundamental Rights European Union, committed by the judicial issuing authority in Bulgaria.